2011
DOI: 10.1080/10916461003699226
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Polycyclic Aromatic Hydrocarbons to Assess the Source and Thermal Maturity of the Crude Oils from the Lower Indus Basin, Pakistan

Abstract: A suite of six crude oils from Lower Indus Basin, Pakistan, were analyzed for geochemical characterization of source organic matter (OM) and thermal maturity. Distribution of polycyclic aromatic hydrocarbons (PAHs), alkylnaphthalenes, alkylphenanthrenes, alkyldibenzothiophenes, and aromatic biomarkers were reported from aromatic fractions of the crude oils. The aromatic hydrocarbons parameters revealed a higher thermal maturity of OM of source rock-generated Lower Indus Basin oils. Calculated vitrinite reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…170,202,209,225 DBFs appear to predominate in freshwater source rocks, terrestrial oils, and coals, 170,209,[225][226][227] whereas their sulfur-heterocyclic counterparts dibenzothiophenes (DBTs) appear to predominate in marine shales and carbonates. 212,227,228 Radke et al (2000), Asif (2010), and Kruge (2000) indicated that the relative abundance of alkyldibenzothiophene (ADBT) compared to alkyldibenzofuran (ADBF) may be used to identify depositional settings (Fig. 16).…”
Section: Aromatic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…170,202,209,225 DBFs appear to predominate in freshwater source rocks, terrestrial oils, and coals, 170,209,[225][226][227] whereas their sulfur-heterocyclic counterparts dibenzothiophenes (DBTs) appear to predominate in marine shales and carbonates. 212,227,228 Radke et al (2000), Asif (2010), and Kruge (2000) indicated that the relative abundance of alkyldibenzothiophene (ADBT) compared to alkyldibenzofuran (ADBF) may be used to identify depositional settings (Fig. 16).…”
Section: Aromatic Compoundsmentioning
confidence: 99%
“…16). 202,205,229 Variations in the relative abundances of uorenes, dibenzofurans, and dibenzothiophenes have been reported to be a reliable indicator of source rock sedimentary settings. 203,230 The concentrations of the dibenzothiophene series were high in marine carbonate source rocks, while those of uorenes and dibenzofurans series were high in freshwater source rocks.…”
Section: Aromatic Compoundsmentioning
confidence: 99%
“…Such information can be provided, for instance, by the n-alkane distribution curve or by the gas chromatography record of the saturated hydrocarbon fraction on a capillary column 4 . A study for source assessment based on the geochemical characterization of organic matter and maturity of the crude oil samples obtained from Lower Indus Basin, Pakistan has indicated two different origins; one contains majorly aquatic source of organic matter and the other has significant share of land plant organic matter 5 . The Goru formation is dominantly shale or mudstone, frequently calcareous.…”
Section: Physico-chemical and Geochemical Correlation Study Of Aliphaticmentioning
confidence: 99%
“…The sample and internal standard (IS) were mixed in the ratio 80:20 and 1 µL was injected into the GC column in a splitless mode. The GC operating conditions were: 60(1)@4 ºC/min-280 (5). Injector and detector (FID) temperatures were 250 and 280 ºC respectively.…”
Section: Physico-chemical and Geochemical Correlation Study Of Aliphaticmentioning
confidence: 99%
“…Previous studies report that the crude oils from Lower Indus Basin are light to highly condensates (Asif et al, 2011;Nazir and Fazeelat, 2011). The crude oils from Lower Indus Basin are characterized by high API gravities, low sulfur contents, waxy and highly paraffinic in nature.…”
Section: Introduction and Geology Of Samplesmentioning
confidence: 97%